Sustainable supply chain collaboration with outsourcing pollutant-reduction service in power industry. (10th June 2018) - Ding, Huiping; Huang, Hua; Tang, Ou
Abstract: In developing countries, coal power plants still play a major role in the power sector and they are considered as a major emission source of air pollution. Strict regulations have compelled the coal power plants to improve environmental performance by reducing carbon emissions and the emission of pollutants. However, due to cost disadvantages, the coal power plants often lack motivation to internalize environmental externalities through investing in green technology. This situation raises a question: is there any alternative to reduce pollutants in operations economically? With a focus on service supply as well as a consideration of government policies, this paper develops a model to investigate the opportunity of outsourcing a pollutant-reduction service to meet the environmental constraint. The service supply chain consists of a coal power plant (end user) and a pollutant-reduction service provider, with the former outsourcing the service to the latter. We study the policy for improving the profit of this service supply chain whereas the benefit allotment is adjusted through outsourcing price negotiation between the two partners. The results show that the green service outsourcing price is interrelated with the government incentive policy which defines the shares of the two partners. Our key contribution lies in integrating the complex factors affecting the supply chain collaboration such as green service, financial feasibility, environmental constraint, government policies, outsourcing price negotiation, and profit sharing. Our research findings have the following implications: considering environmental externalities, the government should motivate the collaboration between supply chain partners; the economic scale of output and sales price subsidy of electricity generation are the primary factors affecting the price of outsourcing green service and, consequently, the allotment of supply chain profits. The study results indicate the collaboration is potentially effective in improving environmental performance. Highlights: We develop a business model of outsourcing pollutant-reduction service in coal power industry. We investigate mechanism of green service outsourcing with environmental constraint. Sustainable supply chain profit allotment is optimized through negotiating outsource price. Effect of government incentive policies on encouraging green service outsource is examined.